Gloria Anzaldúa’s Hemispheric Performativity - Radlwimmer, Romana. author. aut Link
VII, 117 p. 5 illus.
Keywords: This Palgrave Pivot offers new insights into leading Chicana writer Gloria Anzaldúa, investigating the dynamic composition of her texts, and situating her work in a larger hemispheric tendency of performativity emerging at the turn of the millennium. Presenting Anzaldúa as a quintessential figure of feminist and decolonial theory-making in the Americas, this book argues that the Chicana writer articulated her notions on fluctuations through “performative concepts” which did not respect the borders of single texts or editions, but organically grew through them. The offered close readings of Anzaldúa’s published works, drafts, and archive material demonstrate the constant changes and intertwined phases of her literary and conceptual production. Romana Radlwimmer is Professor of Romance Literatures at the Goethe University of Frankfurt, Germany. She has held teaching and research positions in literary and cultural studies at the Universities of Salamanca, Lisbon, Augsburg, and Tübingen, and was a Fulbright Visiting Scholar at the University of Missouri, US. She is the author of Wissen in Bewegung: LatinaKulturtheorie / Literaturtheorie / Epistemologie (2015), and the editor of the volume Transborder Matters: Circulaciones literarias y transformaciones culturales chicanas y mexicanas (2020). She has published numerous peer-reviewed articles in her fields of research.